Relationship Between Emotions and Resilience in the Face of Adversity: A Study on Older Adults in Pakistan - Kanza Chaudhary; Zara Haroon (NUST Journal of Social Sciences and Humanities)
This study aims to investigate the relationship among adverse life events, positive and negative affect, and resilience in older adults. The research further identifies whether positive and/or negative affect serve as a mediator between negative life events and resilience. A sample of N=103 older adults was selected from Lahore, Pakistan through purposeful sampling. Given the unique cultural and socio-economic environment of Pakistan, understanding these relationships can provide insight into the mental well-being of older adults within this geographical region. Data collection measures included the Geriatric Adverse Life Events Scale (GALES), Positive and Negative Affect Schedule (PANAS), Brief Resilience Scale (BRS), and a demographic form. The study used a cross sectional research design. The results revealed significant correlation between resilience and negative life events, as well as positive and negative affect. However, the analysis revealed that affect did not significantly mediate the relationship between negative life events and resilience. Furthermore, gender differences emerged, with females reporting higher negative affect scores and males exhibiting greater resilience. This study emphasizes the importance of prioritizing older adults' mental well-being, especially given the prevalence of negative events in later life.